Application of Realistick Mathematics Educational (RME) Learning Model to Improve Mathematics Learning Activities and Result for Class XI. Students MIA.2 SMA Negeri 1 Sampolawa - Mustapa (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2022)
This study aims to determine the increase in activity and learning outcomes of mathematics by applying the RME learning model for class XI.MIA.2 students of SMA Negeri 1 Sampolawa. The type of research is CAR which consists of two cycles with each cycle consisting of an activity plan, implementation of action, observation, evaluation and reflection. The target of this research is the students of class XI. MIA.2 SMAN 1 Sampolawa totaling  24 students. The types of data obtained are qualitative data and quantitative data consisting of the results of observation sheets and learning test results. The results showed an increase in learning activities  which also                                                                                                                                            had an impact on increasing learning outcomes. In the first cycle 45.83% of student activities were  categorized as quite active, but hat not met the expected target. Meanwhile, in the second cycle, the students were                                                                           really active. Judging from the data on the of achievement of student activities, 91.67% of all students were categorized as very active. Learning mathematics using the RME learning model has a positive impact on                                                                                                                                    improving students' mathematics learning outcomes which are marked by an increase in the average and completeness of student learning outcomes in each stage, namely the first ceacle, student learning completeness is  59,33% with an average value of 74,96 and cicle II learning completeness experienced a significan increase, namely 95,83% of student completed in learning with in average value of 79,38. Thus, it can be concluded that using the RME learning model cant incease the activity and learning outcomes of students in cllas XI. MIA. 2 SMA Negeri 1 Sampolawa.